2009
DOI: 10.1074/jbc.m808061200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Identify Two Distinct Receptor Binding Surfaces of Insulin-like Growth Factor II

Abstract: Very little is known about the residues important for the interaction of insulin-like growth factor II (IGF-II) with the type 1 IGF receptor (IGF-1R) and the insulin receptor (IR). Insulin, to which IGF-II is homologous, is proposed to cross-link opposite halves of the IR dimer through two receptor binding surfaces, site 1 and site 2. In the present study we have analyzed the contribution of IGF-II residues equivalent to insulin's two binding surfaces toward the interaction of IGF-II with the IGF-1R and IR. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 55 publications
5
33
1
Order By: Relevance
“…However, two major mutagenesis efforts have been made to map out the site 2 residues of IGFs: (1) Gauguin et al assigned E9, D12, F16, D53, L54, and E58 as site 2 residues of IGF1, 28 and (2) Alvino et al suggested E12, D15, F19, L53, and L57 as site 2 residues of IGF2. 29 All of these residues are part of the site 2 contacts with the (F1-F2)′ loops in our structural models (Table 1), except for D53 (IGF1), which is also consistent with mutagenesis work, as Ala mutation of D53 does not change the binding affinity of IGF1 for IGF1R. Because we see partial or no contact of D15 (IGF2) with either F2′ or L1, our data leave open the possibility that D15 could be a site 1 residue, as also suggested by Alvino et al 29 This is conceivable based on our IGF1/IGF1RΔβ model because the homologous residue D12 of IGF1 stably interacts with a site 1 residue R59 on the L1 domain in this model.…”
Section: Site 2 Contacts With L2 F1′ and F2′mentioning
confidence: 97%
See 2 more Smart Citations
“…However, two major mutagenesis efforts have been made to map out the site 2 residues of IGFs: (1) Gauguin et al assigned E9, D12, F16, D53, L54, and E58 as site 2 residues of IGF1, 28 and (2) Alvino et al suggested E12, D15, F19, L53, and L57 as site 2 residues of IGF2. 29 All of these residues are part of the site 2 contacts with the (F1-F2)′ loops in our structural models (Table 1), except for D53 (IGF1), which is also consistent with mutagenesis work, as Ala mutation of D53 does not change the binding affinity of IGF1 for IGF1R. Because we see partial or no contact of D15 (IGF2) with either F2′ or L1, our data leave open the possibility that D15 could be a site 1 residue, as also suggested by Alvino et al 29 This is conceivable based on our IGF1/IGF1RΔβ model because the homologous residue D12 of IGF1 stably interacts with a site 1 residue R59 on the L1 domain in this model.…”
Section: Site 2 Contacts With L2 F1′ and F2′mentioning
confidence: 97%
“…However, there is strong indirect evidence from our models in favor of these IGF1R residues as site 2 participants because these (F1-F2)′ residues contact exactly those residues that have been already demonstrated by careful mutagenesis as site 2 contacts on each ligand (vide supra). 28,29 Role of the C-domain and the D-domain of IGF1/IGF2…”
Section: Novel Site 2 Contactsmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-II consists of four domains, B, C, A, and D (the B and A domains are similar to the corresponding domains in insulin) (13). These domains contain residues that are important in binding IGF-1R and IR.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of ligand results in cross-linking of the two receptor halves leading to a structural change and subsequent activation of the tyrosine kinase domain. The residues on IGF-II important for binding the IR site 1 include Val-43, Phe-26, and Tyr-27, whereas residues Glu-12, Phe-19, Leu-53, and Glu-57 contact site 2 (13). In this study, we used modified forms of IGF-II that contained mutations at these sites of interaction.…”
Section: Discussionmentioning
confidence: 99%